2011
DOI: 10.1111/j.1474-9726.2011.00763.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic effects of intra‐abdominal fat in GHRKO mice

Abstract: SUMMARY Mice with targeted deletion of the growth hormone receptor (GHRKO mice) are GH resistant, small, obese, hypoinsulinemic, highly insulin sensitive and remarkably long-lived. To elucidate the unexpected coexistence of adiposity with improved insulin sensitivity and extended longevity, we examined effects of surgical removal of visceral (epididymal and perinephric) fat on metabolic traits related to insulin signaling and longevity. Comparison of results obtained in GHRKO mice and in normal animals from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
131
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 100 publications
(138 citation statements)
references
References 44 publications
7
131
0
Order By: Relevance
“…Previous studies have indicated that long‐lived mice that either are GH‐deficient or exhibit disrupted GH signaling have increased adiposity and systemic high levels of adiponectin (Berryman et al ., 2004; Wang et al ., 2006). The removal of epididymal visceral fat decreased levels of adiponectin and reduced insulin sensitivity in GHR‐KO and Ames dwarf mice (Masternak et al ., 2012; Menon et al ., 2014). In the context that in the absence of GH signaling, visceral fat exerts unexpected beneficial influence on insulin sensitivity (Bartke, 2008), and in this study Ames dwarf mice are resistant to the detrimental effects of HFD, we were interested in determining whether transplantation of visceral fat from Ames dwarf mice fed HFD into control littermates fed the same diet could improve their insulin sensitivity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have indicated that long‐lived mice that either are GH‐deficient or exhibit disrupted GH signaling have increased adiposity and systemic high levels of adiponectin (Berryman et al ., 2004; Wang et al ., 2006). The removal of epididymal visceral fat decreased levels of adiponectin and reduced insulin sensitivity in GHR‐KO and Ames dwarf mice (Masternak et al ., 2012; Menon et al ., 2014). In the context that in the absence of GH signaling, visceral fat exerts unexpected beneficial influence on insulin sensitivity (Bartke, 2008), and in this study Ames dwarf mice are resistant to the detrimental effects of HFD, we were interested in determining whether transplantation of visceral fat from Ames dwarf mice fed HFD into control littermates fed the same diet could improve their insulin sensitivity.…”
Section: Resultsmentioning
confidence: 99%
“…These data complement the reports that the removal of both epididymal and perinephric WAT reduces insulin sensitivity in Ames dwarf (Menon et al ., 2014) and GHR‐KO mice (Masternak et al ., 2012) and suggest that the eWAT transplant from long‐lived mice improves metabolic function in control mice fed HFD hence aids in the protection against the effects of HFD‐induced metabolic dysfunction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Visceral fat removal elevated the respiratory quotient in GHRKO mice, but had the opposite effect in WT mice (Masternak et al ., 2012). These observations suggested that WAT derived from long‐lived strains of mice, that is, good‐quality WAT, can increase whole‐body lipid utilization.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, reduction of intra-abdominal ("visceral") adipose tissue by surgical removal (24) or as a result of CR (12) is associated with a significant improvement in glucose tolerance in mice. Differences in distribution of adipose tissue could, in principle, influence circulating levels of adipocyte-derived cytokines (adipokines) such as adiponectin and resistin (45), which modulate insulin sensitivity. Thus, it has been suggested that enhanced insulin sensitivity of long-lived GHR-KO mice may be due to the altered secretory profile of visceral fat and, in particular, to enhanced adiponectin secretion by these fat depots (45).…”
Section: Discussionmentioning
confidence: 99%